Factors influencing the composition and balance of foals’ microbiota (Research, Society and Development, 2021)
Horses are extremely dependent on the correct functioning of the digestive system for energy production and the performance of their physiological functions. The intestinal microbiota plays a key role in maintaining health, being related to the modulation of the immune system, protection against pathogenic microorganisms and also for obtaining nutrients. Due to the importance of the microbiota in maintaining health from the beginning of life, this review aims to address the early composition, development and factors that influence the intestinal microbiota in foals. A qualitative review was carried out in the main research databases. Data referring to the early microbial colonization suggest that it occurs since intrauterine life, despite the fact that at birth, the foals acquire a large part of the microorganisms that will form its microbiota. The main phyla involved in this process are Proteobacteria, Firmicutes, Actinobacteria and Bacteroidetes, which are aquired from a combination of bacteria present in the feces, vagina and other maternal environments. From birth until the first weeks of life, the microbiota gradually changes due to several factors, which include the composition of food, coprophagy, exposure to different environments and medications. The foal's microbiota becomes more stable in the first and second months of life. It is suggested that changes in the composition (dysbiosis) and diversity of the different phyla are a risk factor for the development of diseases, since the microbiota directly influences the immune system. From advances in sequencing technologies it was possible to investigate the components and factors associated with early colonization of microbiota in horses as well as factors related to the development of dysbiosis and disease. Nevertheless, many facts are still unclear and should be adressed in the future.